Ticagrelor monotherapy after percutaneous coronary intervention in patients with concomitant diabetes mellitus and chronic kidney disease: a TWILIGHT substudy. (14th October 2021) - Cao, D; Baber, U; Dangas, G; Sartori, S; Zhongjie, Z; Giustino, G; Angiolillo, D J; Mehta, S; Gibson, C M; Sardella, G; Sharma, S K; Shlofmitz, R; et al.
Abstract: Background: Diabetes mellitus (DM) and chronic kidney disease (CKD) are established risk factors for cardiovascular events, with patients presenting both conditions being at extremely high risk. P2Y12 inhibitor monotherapy with ticagrelor after a short course of dual antiplatelet therapy has emerged as a bleeding avoidance strategy for high-risk patients undergoing percutaneous coronary intervention (PCI). Purpose: To investigate ischemic and bleeding outcomes associated with ticagrelor monotherapy versus ticagrelor plus aspirin according to the presence or absence of CKD and DM. Methods: The TWILIGHT trial enrolled patients undergoing PCI with a drug-eluting stent who fulfilled at least one clinical and one angiographic high-risk criterion. Both DM and CKD (estimated glomerular filtration rate <60 mL/min/1.73m 2 ) were clinical study entry criteria. Following 3 months of ticagrelor plus aspirin, patients who had been adherent to treatment and free from major adverse events were randomly assigned to either aspirin or placebo in addition to ticagrelor for 1 year. The primary endpoint was Bleeding Academic Research Consortium (BARC) type 2, 3 or 5 bleeding. The key secondary endpoint was the composite of all-cause death, myocardial infarction, or stroke. Net adverse clinical events (NACE) were defined as BARC type 3 or 5 bleeding, all-cause death, myocardial infarction, or stroke. Results: Of the 6273 patients included in the analysis, 8.0% had both CKD and DM (DM+/CKD+), 8.9% had CKD only (DM-/CKD+), 29.0% had DM only (DM+/CKD-), and 52.1% had neither CKD nor DM (DM-/CKD-). At 1-year follow-up, there was a progressive increase in the rates of bleeding and ischemic events according to DM and CKD status (Figure 1). Ticagrelor plus placebo reduced the primary bleeding endpoint as compared with ticagrelor plus aspirin across all study groups, including DM+/CKD+ patients (4.7% vs. 8.7%; HR 0.52, 95% CI 0.25–1.07), with no evidence of heterogeneity (p-interaction=0.68). Similar treatment effects of ticagrelor monotherapy were observed for major BARC type 3 or 5 bleeding (p-interaction=0.17), with DM+/CKD+ patients showing the greatest absolute risk reduction (0.9% vs. 5.1%; HR 0.16, 95% CI 0.04–0.72). The key secondary endpoint was not significantly different between treatment arms across study groups, with the exception of a reduced risk in DM+/CKD- patients receiving ticagrelor monotherapy (p-interaction=0.033). A similar pattern in the DM+/CKD- group was observed for NACE (p-interaction=0.030) (Figure 2). Conclusions: Among high-risk patients undergoing PCI, ticagrelor monotherapy reduced the risk of clinically relevant and major bleeding without a significant increase in ischemic events as compared with ticagrelor plus aspirin, irrespective of the presence of DM and CKD. Furthermore, ticagrelor monotherapy seemed to be associated with a more favourable net benefit in patients with DM without CKD. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Investigator-initiated grant from AstraZeneca